Preparation, physicochemical and microbiological evaluations of italian type salami fermented with kefir (Research, Society and Development, 2021)
Industrialized meat product, known as salami, is composed of some types of meat, such as pork, beef or pork and beef together, added ingredients and bacon. This research aimed to elaborate Italian salami using the fermentation process with standard starter bacteria, such as control, water and milk kefir, and evaluate the physicochemical and microbiological characteristics of the final product. The use of kefir grains aimed to analyze the possibility for their use in the production of salami as starter cultures from their symbiotic association of yeasts, acid-lactic bacteria, acetic bacteria and also their probiotic and antimicrobial action. The microbiological and physicochemical composition indicates that kefir is a product with probiotic characteristics, because it has in its composition living microorganisms capable of improving the intestinal microbial balance producing beneficial effects on the health of the individual who consumes it. At the end of the analyses, it was observed that the salami based on standard starter bacteria culture presented greater diversity of fungi, and the fungus Exophiala spp was present in the 3 types of salamis. The samples showed absence of pathogenic bacteria such as Salmonella ssp, Shigella ssp and E.coli. There was little variation in the physical-chemical characteristics of the salamis evaluated.  It was concluded that kefir can replace industrial fermentation culture without affecting the microbiological and physicochemical pattern of salami.